To Be or Not to Be Scientific Is Not the Question: A Science Scholar’s Challenge for the Study of Religion - Orye, Lieve (Bulletin for the study of religion, 2022)
In The Archive we republish an article that, in hindsight, may have been ahead of its time with its prescience. Our second pull for this issue is a 2005 piece from Lieve Orye where he discusses the intricacies of categorizing religious studies as an art or a science. He endeavors to find out if the field should be studied with a scientific approach. Orye posits that maybe this is not even a question we should be asking. This piece was originally published in Council for the Societies for the Study of Religion Bulletin 34.1-2, 14-18.